Kompensasi, Motivasi dan Disiplin Kerja Terhadap Kinerja Pegawai di RSUD Besuki Kabupaten Situbondo - Imam Hariyono; Ramli Tarigan; Andre Ferdian; Chamariyah Chamariyah (Universitas Methodist Indonesia, 2025)
This research was conducted at Besuki Regional Hospital. This study consists of two variables, namely the independent variable (free) which consists of compensation (x1), work discipline (x2), and work motivation (x3), while the dependent variable (bound) is Employee Performance (y). This study aims to determine whether there is a significant influence between compensation, work discipline, and work motivation on employee performance with a sample of 162 respondents. In this study data collection using interview techniques, observation, questionnaires, and literature study. The data analysis technique in this study uses multiple linear analysis with data processing using statistical product and service solutions (SPSS) software 20. The data analysis methods used are validity test, reliability test, multicollinearity test, heteroscedasticity test, partial t test, f test simultaneous and coefficient of determination (R2). The results of this study indicate that the variables of Compensation, Work Discipline and Work Motivation have a simultaneous influence on employee performance, partially showing that the Compensation and Work Motivation variables have an influence. Based on the results of the analysis of the coefficient of determination, where the value of R square is 0.810 or 81%.